The Study on the Immersive Learning Environment for Teaching Students About Hajj and Umrah - Nur Aqilah Tahir; Nur Syahela Hussien; Masyarah Zulhaida Masmuzidin (Journal of Computing Technologies and Creative Content, 2025)
Even though education keeps experiencing fast revolution from chalk to the computer, most Islamic education are still taught using traditional methods, hence affecting their motivation and achievement levels. This virtual stimulation hajj project proves that using technology could enhance middle school students’ learning motivation with increasing their engagement level and giving them a chance to learn more about Hajj just like the real pilgrimage. Due to the lack of students’ interest and performance when it comes to learn Hajj pilgrimage, one must create a solution for it. Thus, virtual reality has been chosen as its method with reasons. Using systematic literature review as the methodology, three processes are needed to go through – generating research questions, search process of inclusion and exclusion criteria, select and access the literature, data analysis and proposing a research model. The majority of the development’s outcomes have received excellent feedback and comments from its target audience, although additional changes are required. This demonstrates that one of the most suggested learning methods is virtual reality. Future work will include providing a better solution to improve Hajj pilgrims’ virtual learning experience.